2023
DOI: 10.1007/s12072-023-10521-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary long-term consequences of COVID-19: dramatically increased rate of secondary sclerosing cholangitis in critically ill COVID-19 patients

Abstract: Background Increasing evidence suggests that secondary sclerosing cholangitis (SSC), which can lead to cirrhosis or liver failure, may be a hepatobiliary long-term complication of COVID-19. The aim of this study was to estimate the frequency and outcome of this COVID-19 sequela and to identify possible risk factors. Methods This observational study, conducted at University Hospital Charité Berlin and Unfallkrankenhaus Berlin, Germany, involved hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…It most likely occurs when the patient's condition is most critical, i.e., around the time of intubation. Both the peracute onset of post–COVID-19 cholangiopathy and the distribution pattern of bile duct lesions are reminiscent of ischemic cholangitis and confirm our recent findings ( 9 ). PCR testing, although not performed in all of our patients, did not detect any viral components of SARS-COV-2 in the bile.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It most likely occurs when the patient's condition is most critical, i.e., around the time of intubation. Both the peracute onset of post–COVID-19 cholangiopathy and the distribution pattern of bile duct lesions are reminiscent of ischemic cholangitis and confirm our recent findings ( 9 ). PCR testing, although not performed in all of our patients, did not detect any viral components of SARS-COV-2 in the bile.…”
Section: Discussionsupporting
confidence: 91%
“…Other authors postulated that this cholangiopathy observed in patients with COVID-19 was ketamine induced ( 7 ). Exclusively observed in critically ill patients, increasing evidence suggests that post–COVID-19 cholangiopathy is (merely) a variant of secondary sclerosing cholangitis in critically ill patients (SSC-CIP) ( 9 , 10 ). As recently shown, the incidence of this post–COVID-19 cholangiopathy is high—up to 2.3 cases per 100 invasively ventilated patients with COVID-19 ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors identified include signs of systemic reduced blood oxygen supply, multi-organ failure, high fibrinogen levels, and intravenous ketamine use. 84 Additionally, disease severity and the need for ICU admission have been linked to an increased risk of cholangiopathy. 85 These findings suggest that certain demographic and clinical factors contribute to the development of cholangiopathy in individuals affected by COVID-19.…”
Section: Cholangiopathy In Covid-19mentioning
confidence: 99%
“…With great interest, we read the article by Leonhardt et al [ 1 ] describing diverse risk factors for developing secondary sclerosing cholangitis (SSC) following severe Covid-19.…”
mentioning
confidence: 99%